Self-perceived knowledge, attitudes, and training needs regarding medical cannabis among health care providers and health volunteers in district health systems, Phitsanulok Province - Mekrungrongwong, Sunsanee; Kitreerawutiwong, Nithra; Keeratisiroj, Orawan; Jariya, Wutthichai (BMC family practice, 2022)
Background: Health care providers and health volunteers play an important role in the collaborative provision of patient access and care regarding medical cannabis in district health systems (DHSs) according to their roles and responsibilities. However, there is limited evidence on the self-perceived knowledge, attitudes, and training needs regarding medical cannabis use by health care providers and health volunteers in DHSs. The aim of this study was to compare self-perceived knowledge, attitudes, and training needs regarding medical cannabis among health care providers and health volunteers in Phitsanulok Province, Thailand. Methods: A cross-sectional study was conducted in Phitsanulok Province. A total of 836 participants consisting of 166 health care providers and 670 health volunteers were recruited by stratified cluster random sampling. Descriptive and inferential statistics, including independent sample t tests and chi-square tests, were employed for data analyses. Results: The results revealed that self-perceived knowledge of medical cannabis was not significantly different between the health care providers and health volunteers (p = 0.875), whereas attitudes about medical cannabis were significantly different between the two groups (p < 0.001). The mean scores of attitudes were 29.10 for the health care providers and 31.84 for the health volunteers. Regarding training needs, the health care providers proposed training topics, including adverse effects of medical cannabis (27.5%), information on prescribing cannabis drugs (20.5%) and information on prescribing drugs that contain cannabis substances (14.7%). On the other hand, health volunteers preferred to obtain training on cannabis legislation (23.5%), information on caring for patients who used drugs containing cannabis substances (21.4%), and a history of medical cannabis use (17.6%). Conclusion: In summary, to ensure effective care in the DHSs, health care providers and health volunteers should be trained to be confident in their knowledge and attitudes towards the use of medical cannabis. Training topics should be designed with consideration for the role and responsibility of each group to prepare professionals and nonprofessional to achieve patients quality and safety with respect to medical cannabis use.